Corporate governance in China : a study on S-chips - Lim, Sylvia Ying Zhen (2013)
In July 2012 alone, there were a total of nine S-Chip companies under investigation for suspected fraud. Thus, this report was commissioned to examine the increasing trend of S-Chips defaulting.